ANALISIS KINERJA BERDASARKAN BALANCED SCORECARD DEPARTEMEN CAPITAL DAN PROJECT MANAGEMENT PT. VALE INDONESIA TBK DI TAHUN 2015 - Rusmin Muliadi; Cepi Pahlevi; Mursalim Nohong (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Performance appraisal plays an important role in the business world, because with the performance appraisal can be known the effectiveness of the determination of a strategy and its application within a certain period. Performance appraisal can detect weaknesses or deficiencies that still exist within the company, for further improvement in the future. This research was conducted at PT. Vale Indonesia Tbk. Department of Capital and Project Management. Data were collected using questionnaires, interviews, and observations. After all data collected and processed then performed data analysis using Financial Perspective Analysis, Data Analysis Questionnaire, then diguanakan tools balance scorcard. The results of this study can be seen from several aspects that are based on the assessment of customer perspective variables above, the total value of overall customer perspective of 3.49, the financial perspective of Capital and Project Management Department seen from the ratio of liquidity and solvalitas better than the standard size industry. When viewed from the ratio of activities, the collection period is better and total asset turnover is below industry value, while the cost recovery rate of Capital and Project Management Department is above ideal value, the three variables from the process perspective, the overall value of internal business process perspective performance is 3 , 66 which can be categorized good enough, variable of learning perspective and growth above, hence can be calculated value of whole variable of learning and growth perspective equal to 3,68 and the value entered in category enough baik.Balanced Scoreccard can measure performance which include financial perspective, Customer, internal business process perspective, and learning and growth perspective to obtain recapitulation of all aspects.